2020
DOI: 10.1111/and.13777
|View full text |Cite
|
Sign up to set email alerts
|

Do seasonal variations in ambient temperature, humidity and daylight duration affect semen parameters? A retrospective analysis over eight years

Abstract: Natural life depends on biological rhythms that enable living creatures to thrive and survive. Biological rhythms or clocks allow species to adapt their physiological functions to external environmental changes. The environmental changes, creating a complex circadian (day) and circannual (year) rhythmicity, affect the whole organism, particularly the endocrine glands and the gonads. The hypothalamic-pituitary-gonadal axis is extremely susceptible to circannual rhythmicity, regulating the hormone levels (Santi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In terms of insolation duration, animal model studies suggested that seasonal variations may be mediated by endogenous mechanisms related to daylight length [28]. Our data showed that insolation duration had no significant effect on any of the parameters of semen analysis, which is similar to the results of a study in Turkey [29]. It is possible that the effects of sunlight on the change of human semen parameters may be relatively slow, which requires long-term observation and comparison, such as decades or even hundreds of years, or the data of regions with different insolation duration.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of insolation duration, animal model studies suggested that seasonal variations may be mediated by endogenous mechanisms related to daylight length [28]. Our data showed that insolation duration had no significant effect on any of the parameters of semen analysis, which is similar to the results of a study in Turkey [29]. It is possible that the effects of sunlight on the change of human semen parameters may be relatively slow, which requires long-term observation and comparison, such as decades or even hundreds of years, or the data of regions with different insolation duration.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, indoor heating is common in some areas of Henan Province, which may have affected the study results; nevertheless, all patients were inevitably affected by the external environment. Temperature has been shown to be associated with male fertility [30][31][32][33]. In this study, we have excluded men with severe oligozoospermia or teratozoospermia, but still cannot completely rule out the effects of seasonal variation and ambient temperature on semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Similar but non-significant trend was observed regarding sperm concentration and normal morphology rates. This finding can be explained by a natural seasonal fluctuation in the semen quality from the superior winter and spring parameters to lower summer and autumn values (Kabukçu et al, 2020;Levitas et al, 2013;Mao et al, 2017;Wang et al, 2020). Comparing semen parameters throughout the year, Kabukçu et al (2020) Regarding sperm DNA methylation, air pollution was previously reported in association with global sperm DNA hypomethylation (Consales et al, 2016).…”
Section: Resultsmentioning
confidence: 84%
“…This finding can be explained by a natural seasonal fluctuation in the semen quality from the superior winter and spring parameters to lower summer and autumn values (Kabukçu et al, 2020;Levitas et al, 2013;Mao et al, 2017;Wang et al, 2020). Comparing semen parameters throughout the year, Kabukçu et al (2020) Regarding sperm DNA methylation, air pollution was previously reported in association with global sperm DNA hypomethylation (Consales et al, 2016). As for gene-specific changes, exposure to polycyclic aromatic hydrocarbons was found associated with H19 hypomethylation in sperm (Ma et al, 2019).…”
Section: Resultsmentioning
confidence: 87%